2020
DOI: 10.1371/journal.pone.0230567
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and remaining gaps on the role of animal and human movements in the poultry production and trade networks in the global spread of avian influenza viruses – A scoping review

Abstract: Poultry production has significantly increased worldwide, along with the number of avian influenza (AI) outbreaks and the potential threat for human pandemic emergence. The role of wild bird movements in this global spread has been extensively studied while the role of animal, human and fomite movement within commercial poultry production and trade networks remains poorly understood. The aim of this work is to better understand these roles in relation to the different routes of AI spread. A scoping literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“… 2013 ), empirical evidence from the field is lacking (Hautefeuille et al. 2020 ). In Romania, migratory birds appeared to have been responsible for the introduction of the H5N1 virus and its initial spread in the Danube Delta region in the autumn and winter of 2005, but the movement of poultry might have introduced the infection into central Romania during the spring and summer of 2006 (Ward et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2013 ), empirical evidence from the field is lacking (Hautefeuille et al. 2020 ). In Romania, migratory birds appeared to have been responsible for the introduction of the H5N1 virus and its initial spread in the Danube Delta region in the autumn and winter of 2005, but the movement of poultry might have introduced the infection into central Romania during the spring and summer of 2006 (Ward et al.…”
Section: Introductionmentioning
confidence: 99%
“…While the role of animal movements in AIV spread within national trade networks has been largely identified, the risk from human and fomite movements is still largely unknown. Although studies have identified several possible transmission pathways for between-farm transmission, including human movements between poultry houses and other poultry farms (Ssematimba et al 2013), empirical evidence from the field is lacking (Hautefeuille et al 2020). In Romania, migratory birds appeared to have been responsible for the introduction of the H5N1 virus and its initial spread in the Danube Delta region in the autumn and winter of 2005, but the movement of poultry might have introduced the infection into central Romania during the spring and summer of 2006 (Ward et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…And as the information network outside the hospital, the government should disclose information about the disease in time, which would achieve a good promotive and educational effect. 27 …”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of the poultry industry, high-quality poultry meat products are desired by consumers. Researchers need to improve poultry meat quality by exploring the mechanism of muscle development [ 15 , 16 ]. BM-MSCs, which have the potential for myogenic differentiation, can provide critical insights to further understand the potential molecular mechanism in muscle development [ 9 ].…”
Section: Discussionmentioning
confidence: 99%